Temperature Stable Dielectric Properties in BaTiO3–Bi(Mg2/3Nb1/3)O3–NaNbO3 Solid Solution. Issue 12 (26th March 2020) - Muhammad, Raz; Ali, Asif; Camargo, Javier; Castro, Miriam S.
Abstract: 0.5BaTiO3 –(0.5– x )Bi(Mg2/3 Nb1/3 )O3 – x NaNbO3 ( x =0.1, 0.2 and 0.3) samples were processed via solid‐state sintering route. Phase identification of the samples showed the formation of a single‐phase cubic perovskite‐structure (space group Pm ‐3  m ) which was further confirmed using Raman spectroscopy. Microstructural analysis of the samples revealed some voids in the samples while grain size was observed to decrease with increasing NaNbO3 concentration. The addition of NaNbO3 shifted T m to below room temperature and the stability range of 0.5BaTiO3 –0.5Bi(Mg2/3 Nb1/3 )O3 ceramics was enhanced. The sample with x =0.20 exhibited ϵr(mid) = 400 ±15% stable over a wide temperature range from −85 to 500 °C and most importantly a low dielectric loss of < 0.05 stable across a wide temperature range −100 to 426 °C was maintained. The thermally stable dielectric properties of sample x =0.2 suggests that it could be useful candidate material for capacitor applications in both low (X9R) as well as harsh environment applications. Abstract : Na + and Nb 5+ doped BT–BMN (BaTiO3 –Bi(Mg2/3 Nb1/3 O3 )) ceramics were processed via solid state route which had a cubic crystal structure. 20 mol.% doped sample exhibited excellent temperature stable dielectric properties which suggest that the sample could be a good candidate material for developing multilayer ceramics capacitors for both X9R and harsh environment applications.